2006
DOI: 10.1038/sj.bjc.6603431
|View full text |Cite
|
Sign up to set email alerts
|

Periostin is frequently overexpressed and enhances invasion and angiogenesis in oral cancer

Abstract: Oral squamous-cell carcinoma (OSCC) is one of the most common types of human cancer. Typically OSCC cells show persistent invasion that frequently leads to local recurrence and distant lymphatic metastasis. We previously identified Periostin as the gene demonstrating the highest fold change expression in the invasive clone by comparing the transcriptional profile of parent OSCC cell line and a highly invasive clone. Here, we demonstrated that Periostin overexpression enhanced invasiveness in oral cancer cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
125
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(140 citation statements)
references
References 26 publications
9
125
3
Order By: Relevance
“…Previous studies showed that periostin was up-regulated in various types of cancers such as the lung, 26 brain, 8 ovary, 9 breast, 27 colon 11 and oral cavity, 28,29 and its serum level was reported to be high in patients with thymoma, 30 non-small cell lung cancer 10 and breast cancer. 31 These reports suggested that periostin is involved in tumor spread, invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that periostin was up-regulated in various types of cancers such as the lung, 26 brain, 8 ovary, 9 breast, 27 colon 11 and oral cavity, 28,29 and its serum level was reported to be high in patients with thymoma, 30 non-small cell lung cancer 10 and breast cancer. 31 These reports suggested that periostin is involved in tumor spread, invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown by serial analysis of gene expression (SAGE) and multiple genome-wide microarrays that human periostin gene is overexpressed in several human tumors including carcinomas of ovary, breast, pancreas and head and neck squamous cell carcinoma (26)(27)(28)(29)(30). On the other hand, acquired expression of periostin by cancer cells greatly promotes metastatic development, adhesion and invasion of cancer cell lines (7,8,12,13,15). Cumulative findings suggest that high expression of periostin might be a common event in tumor development.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas integrin expression level is supposed to be related to metastasis, relapse and prognosis of CRC (10,11). In addition, expression of periostin is reported to be elevated in certain malignant tumors including head and neck cancer (12,13), nasopharyngeal carcinoma (14), breast cancer (15)(16)(17), CRC (7), and pancreatic carcinoma (9,18). Circulating levels of periostin was found to be elevated in thymoma, breast cancer with bone metastases, and pancreatic carcinoma (9,(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Also, PN is reported to be up-regulated in the metastases of colorectal and liver cancers, suggesting its role in promoting tumor growth. Increased expression of PN has been associated with advanced carcinogenesis and cell proliferation, adhesion and migration (6)(7)(8). PN expression was readily detectable in breast tumor samples, while it was undetectable in normal breast tissue (9).…”
Section: Introductionmentioning
confidence: 96%